Pengaruh Penggunaan Media Pembelajaran dan Model Pembelajaran terhadap Pemahaman Siswa SD/MI - Didit Darmawan; Abidhatul Khoiroh; Annisa Sucimariyana (Konsorsium Dosen Institut Agama Islam Al-Yasini Pasuruan, 2026)
One of the key pillars for the development of knowledge, abilities, and expertise that people possess in order to cultivate their capabilities and adjust to a constantly changing environment is education. The purpose of this literature review is to investigate how primary school students' comprehension is affected by the use of learning models and learning media. This study employs a qualitative methodology and a literature review technique to investigate how primary school students' comprehension is affected by the use of learning models and learning media. The findings demonstrate that the use of interactive learning models in conjunction with appropriate learning media has a beneficial impact on raising student comprehension. Pupils are more engaged in the learning process, have better conceptual understanding, and find it simpler to relate the subject to real-world situations. Therefore, it can be concluded that promoting learning success at the primary school level is greatly aided by the combination of suitable learning media and learning models.